Predictors of Right Ventricle Dysfunction After Anterior Myocardial Infarction - Gaiolla, Paula Schmidt Azevedo [UNESP]; Cogni, Ana Lucia [UNESP]; Farah, Elaine [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Zanati, Silmeia G. [UNESP]; Fonseca, Ana Gabriela N. [UNESP]; Patini, Bruno J. T. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Elsevier B.V., 2012)
Background: Regardless significant therapeutic advances, mortality and morbidity after myocardial infarction (MI) are still high. For a long time, the importance of right ventricle (RV) function has been neglected. Recently, RV dysfunction has also been associated with poor outcomes in the setting of heart failure. The shape, location, and contraction conditions make the RV chamber assessment technically challenging.Methods: Our study identified clinical characteristics and left ventricle (LV) echocardiographic data performed 3-5 days after MI that could be associated with RV dysfunction (RV fractional area change [FAC] < 35%) 6 months after MI.Results: The RV dysfunction group consisted of 11 patients (RV FAC 29.4% +/- 5.2) and the no RV dysfunction group of 71 patients (RV FAC 43.7% +/- 5.1); (P < 0.001). Both groups presented the same baseline clinical characteristics. Left atrium (LA), interventricular septum (IVS), and left ventricular posterior wall (LVPW) were larger in RV dysfunction than in no RV dysfunction. Conversely, E wave deceleration time (EDT) was lower in RV dysfunction when compared with no RV dysfunction. Left atrium(adj) (adjusted by gender, age, infarct size, and body mass index) (odds ratio [OR], 1.22; confidence interval [CI], 1.016-1.47; P = 0.032), interventricular septum(adj) (OR, 1.49; CI, 1.01-2.23; P = 0.044), and E wave deceleration time(adj) (OR, 0.98; CI, 0.97-0.98; P = 0.029) assessed soon after MI predicted RV failure after 6-months.Conclusions: LV diastolic dysfunction, resulting from anterior MI and assessed 3-5 days after the event, may play an important role in predicting RV dysfunction 6 months later.